2011
DOI: 10.1007/s12600-011-0193-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Banana bract mosaic virus on cardamom

Abstract: During a survey for mosaic disease caused by Cardamom mosaic virus (CdMV) in cardamom plantations, a new kind of viral disease showing chlorotic streak on veins was observed in some plantations. Based on the type of symptom, the disease was named 'chlorotic streak'. In a survey of 77 cardamom plantations at 49 locations in the states of Kerala, Karnataka and Tamil Nadu in India, incidence of the disease ranged from zero to 15%. The plants infected with chlorotic streak tested negative in reverse transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…Pentalonia nigronervosa, Rhopalosiphum maidis, and Aphis gossypii [11]. The main host of BBrMV is Musa and recently, BBrMV is reported in small cardamom (Elettaria cardamomum) in India [20] and also infects flowering ginger, Alpinia purpurata (Vieill.) K. Schum in Hawaii [25].…”
Section: Introductionmentioning
confidence: 99%
“…Pentalonia nigronervosa, Rhopalosiphum maidis, and Aphis gossypii [11]. The main host of BBrMV is Musa and recently, BBrMV is reported in small cardamom (Elettaria cardamomum) in India [20] and also infects flowering ginger, Alpinia purpurata (Vieill.) K. Schum in Hawaii [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is native of evergreen forests of Western Ghats of South India [6]. Mosaic/katte disease caused by Cardamom mosaic virus (CdMV) (genus: Macluravirus) and chlorotic streak disease caused by Banana bract mosaic virus (BBrMV) (genus: Potyvirus) are the major viral diseases affecting the crop [3,10]. The mosaic disease is characterized by interveinal prominent discontinuous yellowish stripes running out from midrib to the margin of leaves [12].…”
mentioning
confidence: 99%
“…Crop losses of 10-60, 26-91 and 82-92 % were reported in first, second and third years of production, respectively [14]. The chlorotic streak disease is characterized by continuous or discontinuous intraveinal chlorotic streak with an incidence ranging from 0 to 15 % in the plantations where either banana was grown nearby or banana was the previous crop [10]. Coat protein gene sequence studies of different isolates revealed that CdMV as variable (identity ranging from 74.8 to 99.3 %) [4,11] while BBrMV was highly conserved (97-99 %) [10].…”
mentioning
confidence: 99%
See 2 more Smart Citations